Dental caries and Oral hygiene status among primary school children in Quetta, Pakistan: a quantitative approach - Khail, Ashfaq Ahmed Khawaja; Ronis, Katrina; Mureed, Sheh (Journal of the Pakistan Medical Association, 2022)
This study was conducted to ascertain the extent of dental caries among primary school children in Quetta. A total of 362 children were examined for their dental and oral hygiene status. WHO recommended indexes, including Oral Hygiene Index-Simplified (OHI-S) and Decayed, Missing, and Filled Teeth (DMFT), were used for dental examinations. The study results reveal a high prevalence of dental caries (74%), and the mean “DMFT” score was 1.07±1.63, and “deft” score 2.29± 2.31. There were no significant differences among mean deft, gender, and type of school (P=.27 and .07) in deciduous dentition. Public school children were approximately two times more likely to have dental caries (OR 1.92; P=.021). Dental caries were significantly higher among children with poor oral hygiene (OR 2.40; P=.005). Overall, the treatment needs of the children were noted to be over 90%. Keywords: Dental caries, Oral hygiene, Primary schools.